2015
DOI: 10.1038/jp.2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Failed endotracheal intubation and adverse outcomes among extremely low birth weight infants

Abstract: OBJECTIVETo quantify the importance of successful endotracheal intubation on the first attempt among extremely low birth weight (ELBW) infants who require resuscitation after delivery.STUDY DESIGNA retrospective chart review was conducted for all ELBW infants ≤1000 g born between January 2007 and May 2014 at a level IV neonatal intensive care unit. Infants were included if intubation was attempted during the first five minutes of life, or if intubation was attempted during the first 10 minutes of life with hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 23 publications
4
52
2
1
Order By: Relevance
“…The effect of these immediate airway management outcomes on NICU outcomes or neurodevelopmental impact has not been reported on a large scale. One small single‐center retrospective study (n = 88) reports a strong association between first laryngoscopy attempt success within 10 minutes of life and better neurodevelopmental outcomes among extremely very low birthweight infants (ie, birthweight ≤ 1000g): death or neurodevelopmental impairment 29% in infants with first‐attempt success versus 53% in infants with multiple laryngoscopy attempts, unadjusted odds ratio 0.4, 95% CI 0.1‐1.0, P < .05 …”
Section: Airway Management In the Pediatric Icu Emergency Departmentmentioning
confidence: 99%
“…The effect of these immediate airway management outcomes on NICU outcomes or neurodevelopmental impact has not been reported on a large scale. One small single‐center retrospective study (n = 88) reports a strong association between first laryngoscopy attempt success within 10 minutes of life and better neurodevelopmental outcomes among extremely very low birthweight infants (ie, birthweight ≤ 1000g): death or neurodevelopmental impairment 29% in infants with first‐attempt success versus 53% in infants with multiple laryngoscopy attempts, unadjusted odds ratio 0.4, 95% CI 0.1‐1.0, P < .05 …”
Section: Airway Management In the Pediatric Icu Emergency Departmentmentioning
confidence: 99%
“…Moreover, the average time to determine ETT placement was much longer for failed attempts, 61 (47-85 ), than for successful attempts, 47 (37-55 [28-160]). The median time to recommence ventilation after intubation was similar for successful attempts, 5(4-8 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]), and withdrawn attempts, 5 (3-5 [2-38]), but much longer for failed attempts, 28 (17-56 [8-223]). …”
Section: Resultsmentioning
confidence: 99%
“…Another recent retrospective chart looked at 88 extremely low birth weight infants that were intubated in the delivery room during the first ten minutes after birth. Those infants who needed more than one attempt at intubation for successful placement of the endotracheal tube had a greater likelihood of death or neurodevelopmental impairment15. A randomized control trial from 2006 showed that successful intubations with fewer attempts occur more often in infants who received premedication which included a paralytic agent16.…”
Section: Discussionmentioning
confidence: 99%